Two new species of Harmostes (Harmostes) Burmeister (Hemiptera: Heteroptera: Rhopalidae) from Argentina - Melo, María Cecilia (2011)
The family Rhopalidae has been poorly studied in Argentina. Thirty-three species have been recorded, among them 15 species belonging to the genus Harmostes Burmeister. This genus was revised by Göllner-Scheiding (1978) who divided it into two subgenera, H. (Harmostes) and H. (Neoharmostes), based mainly on characteristics of the hemelytra. Here we describe two new species of H. (Harmostes) from Argentina: H. (H.) bilobatus sp. n. and H. (H.) rubrum sp. n. Illustrations of the diagnostic characters and a key to the Argentinean species of the subgenus Harmostes are presented.